3,9-Bis(2-chlorophenyl)-2,4,8,10-tetraoxaspiro[5.5]undecane - Wang, X.Y.; Shi, J.H.; Zhang, M.; Ng, S.W. (International Union of Crystallography, 2010)
The complete molecule of the title compound, C(19)H(18)Cl(2)O(4), is generated by a crystallographic twofold axis that passes through the spiro C atom. The 1,3-dioxane ring adopts a chair conformation and the phenyl substituent occupies an equatorial site.